Experimentação-vida: a poesia de Antonio Brasileiro - Santana Filho, Valdomiro Ferreira (2008)
This is a study on the poetry of Antonio Brasileiro, author born in 1944 in Rui Barbosa, Bahia, Brazil. His poetic work, which began to be written in 1965, which currently comprises nine books, has been well received by the public and criticism, both in Bahia as in Brazil and abroad. From this work seven poems were selected, among the most significant, which are subject of analysis. The term "life-experimentation" from the title is inspired by the thought of German philosopher Friedrich Nietzsche [1844-1900]. Three French contemporary thinkers, Maurice Blanchot, Michel Foucault and Gilles Deleuze, are fundamental references of the study. Of these thinkers, who are neonietzschian, each in its own way, working with the concepts of experience, living approach, sensation, becoming, map, multiplicity, repetition and difference. In the light of these concepts, their weft, comes to what Nietzsche called the “eternal return” and “will to power” in their criticism of the “desire for truth” of science and moral. Accordingly, the reading of Brasileiro’s poems doesn’t aim to understand them and / or interpret them, but try them while creating sensitive clusters. Also it shows the relationship that his poetry has with the philosophy, the arts, music and cinema. Since Brasileiro considers himself both painter and poet, a reference to its plastic creation is one of the parts of this dissertative study, which is divided into four chapters. Among them is based a game of reiterations, additions and modulations. In one of the Appendices, there is an interview that the author of the dissertation did with Brasileiro in November 30, 2006.